Self-piercing riveted-bonded hybrid joining of carbon fibre reinforced polymers and aluminium alloy sheets. (November 2019) - Liu, Yang; Zhuang, Weimin
Abstract: The mechanical properties and failure mechanisms of self-piercing riveted-bonded hybrid joints with carbon fibre reinforced polymers (CFRP)/aluminium alloy 5754 are investigated. The effects of the sheet thickness and the ply angle of CFRP on the joints performance are analysed. Tensile shear tests were performed to determine the mechanical behaviour and failure modes of different joints. The failure fractures in the rivet holes were analysed by a scanning electron microscope to characterize the various damage mechanisms of the CFRP. The results show that the joints with 0°/90° ply had the optimum mechanical properties and failed by adhesive and locked structure failure, while fibre fractures, matrix cracks and delamination of CFRP were common in the joints with ±45° ply or complex angle ply. Numerous fibre fractures and fibre peeling occurred in the rivet holes of the joints with complex angle ply, causing serious damage in the bearing region; these joints had the poorest energy absorption capacity. Increasing the CFRP thickness significantly enhanced the strength of the ±45° ply joints and significantly increased the energy absorption of the joints with complex angle ply. Highlights: Research on self-piercing riveted-bonded hybrid joints in CFRP and aluminum alloy sheets. The effects of the sheet thickness and the ply angle of CFRP on the joints performance were studied. The failure surfaces were examined by SEM to analyze the damage mechanisms of CFRP in the rivet hole.